No waves from surface knowledge: diving into the social representations of the deep sea. Issue 1 (2nd January 2022) - Morais, Carla; Moreira, Luciano; Teixeira, Ana Sofia; Aguiar, Teresa
ABSTRACT : Recently, new data about deep-sea ecosystems has stirred scientific, economic, and ecological agendas, but little is known about the public's perspectives of the deep sea. Our goal is to explore the public's common sense knowledge of the deep sea, with a view to inform science communication efforts. Based on social representations theory, we investigated the relationship between the public's meanings associated with the deep sea and psychosocial and positional variables, such as attitudes and education level, and reflected on the implications of the findings for science communication. The study was conducted in Portugal, a coastal, sea-connected country. The sample consisted of 315 adults from different age groups and social strata. Participants were asked to elicit and rank their thoughts about the deep sea using a ranked association technique and fill in questions about sociodemographic information, perceptions, and attitudes concerning the deep sea. Results showed that the social representations of the deep sea were structured as emotional versus rational views and as superficial ocean knowledge versus novel or unusual views. Moreover, results evinced a relationship between representations and psychosocial and positional variables. The gap between scientific and common sense knowledge was evident amongst participants with a low education level and low science engagement, whilst highly educated and science-engaged participants' representations seemed to be narrowed by instrumental views on science. This research is significant to better directing science communication to increase well-informed public participation in decision-making related to deep sea management and other socio-scientific issues by responding to audience's background knowledge.